5-Norbornene-2-carboxylic acid: Another catalytic mediator for Catellani-type reactions. Issue 12 (22nd March 2019) - Liu, Ze-Shui; Qian, Guangyin; Gao, Qianwen; Wang, Peng; Cheng, Hong-Gang; Hua, Yu; Zhou, Qianghui
Abstract: Mediators play a central role in Catellani-type reactions. Herein we reported the discovery of inexpensive 5-norbornene-2-carboxylic acid (N 4 ) as a general catalytic mediator (20 mol%) to facilitate ortho C–H activation and the following C–C bond formation of aryl iodides. Firstly, a cooperative catalytic system comprisingN 4 and a palladium/XPhos complex was developed for the novel Catellani/redox-relay Heck cascade to construct tetrahydronaphthalenes and indanes that contain a quaternary carbon stereogenic center. The striking feature of this work was the avoidance of stoichiometric NBE mediator that are usually required for Catellani-type reactions. Then, preliminary results demonstrated thatN 4 could act as a general catalytic mediator to replace NBE for other Catellani-type reactions, which will undoubtedly inspire future developments in the field of cooperative catalysis. Finally, control experiments indicated that the carboxylic acid moiety ofN 4 plays an essential role in its ability to serve as a superior mediator. Graphical abstract: Image 1